Analysis of antimicrobial consumption in critical patients in a reference hospital in Piauí (Research, Society and Development, 2020)
Antimicrobials are one of the most widely prescribed classes of drugs worldwide. Due to the large number of occurrences of Health care-associated infections (HAIs), the most diverse classes of these drugs are used and this problem becomes more serious in the Intensive Care Unit (ICU), which is considered an ideal environment for HAIs. The main objective of this study was to analyze the profile of antimicrobial consumption in patients in the Intensive Care Unit of a state public hospital and the consequences of the use of these drugs on kidney function. It is a retrospective quantitative study, including only information contained in the database of patients admitted from January 1 to March 31, 2019, who consumed at least one antimicrobial. The data were recorded in Microsoft Excel spreadsheets and analyzed using relative and absolute frequencies. A higher consumption of carbapenems and a higher prevalence of the microorganism Acinetobacter baumannii were observed, which confirms its rapid dissemination. 46.94% of the patients had impaired kidney functions. In view of this, the importance of a pharmacist in the ICU is demonstrated as he contributes to the review of pharmacotherapy, besides assisting with strategies in choosing the right antimicrobials at doses tolerated by the patient.